Teen parents' life at the fast lane design template for teen pregnancy prevention campaign posters - Santos, Katherine Kaye V.
This thesis paper presented information on the issue of teen pregnancy, its inherent risks, and probable recommended action. This paper however focuses more on the media intervention and their contributions in campaigns to help create support for awareness and information dissemination. It explores the promising roles that the media could play in the campaign. The design templates for teen pregnancy prevention campaign posters undergo a three-step creative process to develop an effective campaign. It uses the poster as medium and applied different visual elements in the process. Through book research, literature s and interviews, needed information were gathered and served as the groundings for the concept making. It has been found out that posters become obvious focal points because of their sizes and their content. The use of photographs, slogan, and tagline are also creating greater awareness on teen pregnancy prevention. Messages of the posters basically respond to audience needs and interests. It also use threat appraisal by providing convincing evidence. To support threats, dramatized case examples were shown through realistic depiction of the teenagers' lives before and after teen pregnancy. Each poster has become a manifestation of their real situation, thus giving human face to the issue of teen pregnancy.